Evaluation of various options for resurfacing of soft-tissue defects of dorsum of hand and their outcome assessment - Sasanka Nath; Subhashis Karmakar; Dipankar Mukherjee; Amitesh Kumar Jha (Asian Journal of Medical Sciences, 2022)
Background: Soft tissue defect of dorsum of hand is a difficult problem to deal with in reconstructive surgery. Various factors have to be considered for planning of the reconstruction. Aims and Objectives: To assess the overall incidence of soft tissue defect on dorsum of hand, evaluation of different options for coverage of soft tissue defect on dorsum of hand, assessment of outcome and complications (both primary and donor sites) of reconstructive procedures and coverage of defect with like for like tissue. Materials and Methods: We present our experience of resurfacing soft-tissue defects of dorsum of hand in 27 patients by split thickness skin grafting, local flaps, distant pedicled flaps, and free flaps. Results: Among total 27 patients, in whom resurfacing was done, distant pedicled flaps such as groin/abdominal flap were performed in 13 patients, regional flaps like posterior interosseous artery flap were done in seven patients, free flap like anterolateral thigh flap was the method in three patients, and skin grafting was used in two patients. Complications such as partial or complete flap necrosis were noted in one patient each of free and regional flap and none in distant pedicled flap. The operating time was relatively less in distant pedicled flaps. Conclusion: Skin grafting had limited use when underlying vital structures were exposed. Distant pedicled flaps such groin and abdominal flaps were very useful for resurfacing the defect especially in emergency situations. Regional and free flaps had limited indications.